Pengaruh Pertumbuhan Penjualan, Likuiditas, Dan Aktivitas Terhadap Kebijakan Dividen Pada PT Semen Indonesia (Persero) Tbk Periode 2015-2024 - Sri Mulyati; Eni Puji Astuti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of sales growth, liquidity, and activity on dividend policy, both partially and simultaneously. The sample of this study is the balance sheet, income statement, and statement of changes in equity of PT Semen Indonesia (Persero) Tbk from 2015 to 2024. The analysis method the methods used in this study are descriptive statistical analysis, classical assumption test, multiple linear regression, coefficient of determination, t test, and f test using the IBM SPSS version 26 application. The results of this study indicate that: 1) sales growth does not affect dividend policy (DPR), 2) liquidity (CR) does not affect dividend policy (DPR), 3) activity (WCTO) does not affect dividend policy (DPR). The results of the t test on the sales growth variable obtained a calculated t of 0.729 with a probability of 0.943 whose value is above 0.05. Thus, H1 is rejected, which means there is no influence between the sales growth variable partially on dividend policy. The results of the t test on the liquidity variable obtained a calculated t of -0.766 with a probability of 0.473 whose value is above 0.05. Thus, H2 is rejected, which means there is no influence between the liquidity variable partially on dividend policy. The t-test results for the activity variable obtained a calculated t of -0.369 with a probability of 0.725, which is above 0.05. Thus, H3 is rejected, meaning there is no partial influence between the activity variable and dividend policy. The f-test results show that sales growth, liquidity, and activity do not have a significant effect on dividend policy, with a probability value of 0.798, which is greater than the significance level of 0.05. Thus, H0 accepted and Ha rejected, which means there is no influence between sales growth, liquidity and activity simultaneously on dividend policy